Influence of nearest-neighbor Coulomb interactions on the phase diagram of the ferromagnetic Kondo model - Malvezzi, André Luiz [UNESP] (American Physical Society (APS), 1999)
The influence of a nearest-neighbor Coulomb repulsion of strength V on the properties of the ferromagnetic Kondo model is analyzed using computational techniques. The Hamiltonian studied here is defined on a chain using localized S = 1/2 spins, and one orbital per site. Special emphasis is given to the influence of the Coulomb repulsion on the regions of phase separation recently discovered in this family of models, as well as on the double-exchange-induced ferromagnetic ground state. When phase separation dominates at V= 0, the Coulomb interaction breaks the large domains of the two competing phases into small islands of one phase embedded into the other. This is in agreement with several experimental results, as discussed in the text. Vestiges of the original phase separation regime are found in the spin structure factor as incommensurate peaks, even at large values of V. In the ferromagnetic regime close to density n = 0.5, the Coulomb interaction induces tendencies to charge ordering without altering the fully polarized character of the state. This regime of charge-ordered ferromagnetism may be related with experimental observations of a similar phase by Chen and Cheong [Phys. Rev. Lett. 76, 4042 (1996)]. Our results reinforce the recently introduced notion [see, e.g., S. Yunoki et al., Phys. Rev. Lett. 80, 845 (1998)] that in realistic models for manganites analyzed with unbiased many-body techniques, the ground state properties arise from a competition between ferromagnetism and phase-separation - charge-ordering tendencies. ©1999 The American Physical Society.